Endometrial Glandular Atypia and its Association with Pelvic Adhesions and Operative Complexity Across Gynecological and Urological Systems - Saima Khattak, Sajid Ali Ahmad, Kausar Masoom, Farah Saleem, Syeda Ayesha Alam, Faizan Godil (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Endometrial glandular atypia (EGA) is a premalignant endometrial lesion often associated with abnormal bleeding and chronic pelvic symptoms. Its potential contribution to pelvic adhesion formation and increased operative complexity across gynecological and urological systems remains underexplored. Objective: To evaluate the association between endometrial glandular atypia, severity of pelvic adhesions, and operative complexity among women undergoing gynecological and combined gyne-urological surgeries. Methods: A cross-sectional observational study was conducted at Lady Reading Hospital, Peshawar, and Dr. Faisal Masood Teaching Hospital, Sargodha, from June 2022 to June 2023. Ninety women undergoing pelvic surgery were enrolled and divided into two equal groups based on postoperative histopathology: EGA-positive (n=45) and EGA-negative controls (n=45). Pelvic adhesions were graded intraoperatively using the Modified American Fertility Society (mAFS) classification. Operative complexity was assessed through operative time, estimated blood loss, surgeon-reported difficulty scores, and requirement for urological assistance. Statistical analysis was performed using SPSS v25, with p-values <0.05 considered significant. Results: Women with EGA demonstrated significantly higher rates of moderate-to-severe adhesions (62.2% vs. 28.8%; p=0.002). Mean operative time was longer in the EGA group (121 ± 25 minutes vs. 94 ± 18 minutes; p<0.001), and intraoperative blood loss was greater (254 ± 70 mL vs. 182 ± 48 mL; p<0.001). A greater proportion of EGA patients received high difficulty scores (57.7% vs. 22.2%; p<0.001). Urological involvement, including ureterolysis and difficult bladder dissection, was significantly more common in the EGA group (28.8% vs. 8.8%; p=0.01). A strong positive correlation was found between EGA and adhesion severity (r=0.63, p<0.001). Conclusion: Endometrial glandular atypia is significantly associated with increased pelvic adhesion burden and greater operative complexity in gynecologic and urologic surgeries. Preoperative identification of EGA may assist clinicians in anticipating surgical challenges, optimizing operative planning, and involving urology specialists to reduce intraoperative risks. Keywords: Endometrial glandular atypia, pelvic adhesions, operative complexity, ureterolysis, gynecology, urology, pelvic surgery.